2020
DOI: 10.1159/000509944
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and Proteomics Reveal the Variation of Substances in Apheresis Platelets during Storage and Their Effects on Cancer Cell Proliferation

Abstract: <b><i>Introduction:</i></b> Apheresis platelets (APs) are clinically and crucially important in the prevention and treatment of bleeding in patients with thrombocytopenia or cancer. However, few researchers have addressed the variation of supernatant metabolites and exosome proteins in APs during storage and their effects on cancer cell proliferation. <b><i>Objective:</i></b> This study was designed to explore the change rules of the metabolites and exosomal prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…37,38 Our previous experiments confirmed that the exosomes of platelets have no obvious effect on tumor proliferation, while the supernatant has an inhibitory effect on tumor cells, which also shows the dual effect of preserved platelets on tumors. 14,15 Contrary to previous reports, our study showed that PMPs may act in different ways on different tumor cells, PMPs promoted the invasion and metastasis of HCC cells, and hardly caused apoptosis, which also ensured the escape of HCC cells.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…37,38 Our previous experiments confirmed that the exosomes of platelets have no obvious effect on tumor proliferation, while the supernatant has an inhibitory effect on tumor cells, which also shows the dual effect of preserved platelets on tumors. 14,15 Contrary to previous reports, our study showed that PMPs may act in different ways on different tumor cells, PMPs promoted the invasion and metastasis of HCC cells, and hardly caused apoptosis, which also ensured the escape of HCC cells.…”
Section: Discussioncontrasting
confidence: 99%
“…[11][12][13] In our previous study, we found that substances released during APs preservation were involved in the process of cancer cells. 14,15 Therefore, we focused on the study of the changes in the content of a small fraction of microparticles released by APs in the Chinese population. The study of microparticles released during platelet preservation has an important reference basis for improving platelet preparation, storage conditions and transportation, and has important clinical significance for guiding the clinical transfusion of APs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apheresis platelet (AP) transfusion, as a potentially life-saving treatment, is commonly employed to address bleeding complications associated with thrombocytopenia [ 6 ]. APs, obtained from a single donor, possess high platelet concentration, purity, and allow precise control of the infusion dose [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 A number of metabolomic studies have been published using apheresis platelets and have characterized the metabolomic profiles of both the plasma fraction of apheresis platelets and the metabolomic profiles of the platelets themselves and have looked at the differences imparted by routine storage, cold storage, additive solutions, and donor sex. [10][11][12][13][14][15][16] Apheresis platelets are biologically relevant and represent a life-saving therapy for those patients requiring extended surgeries, organ transplantation, myelotoxic chemotherapy, and bone marrow transplantation and the severely injured. Previous studies have shown a significant impact of apheresis versus buffy coat platelet collection procedures on the metabolome of platelets for transfusion purposes.…”
Section: Introductionmentioning
confidence: 99%